2021
DOI: 10.1021/acscatal.1c01738
|View full text |Cite
|
Sign up to set email alerts
|

Supported Molybdenum Carbide Nanoparticles as an Excellent Catalyst for CO2 Hydrogenation

Abstract: Experiments under controlled conditions show that MoC x nanoclusters supported on an inert Au(111) support are efficient catalysts for CO2 conversion, although with a prominent role of stoichiometry. In particular, C-deficient nanoparticles directly dissociate CO2 and rapidly become deactivated. On the contrary, nearly stoichiometric nanoparticles reversibly adsorb/desorb CO2 and, after exposure to hydrogen, CO2 converts predominantly to CO with a significant amount of methanol and no methane or other alkanes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 42 publications
4
38
0
Order By: Relevance
“…Transition-metal carbides are appealing supports for the dispersion of noble metals, and related catalysts exhibit extraordinary reactivity in many reactions, including CO 2 catalytic conversion. 57–61 The substantial importance of transition-metal carbides was highlighted to modify the electronic property of precious metals and then the activity of the catalysts in CO 2 adsorption and activation can be tuned. Transition-metal carbides can also act as co-catalysts to drive the reactions 10 and some of them bind CO 2 strongly and can then induce the cleavage of C–O bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Transition-metal carbides are appealing supports for the dispersion of noble metals, and related catalysts exhibit extraordinary reactivity in many reactions, including CO 2 catalytic conversion. 57–61 The substantial importance of transition-metal carbides was highlighted to modify the electronic property of precious metals and then the activity of the catalysts in CO 2 adsorption and activation can be tuned. Transition-metal carbides can also act as co-catalysts to drive the reactions 10 and some of them bind CO 2 strongly and can then induce the cleavage of C–O bonds.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, it has been shown that this pitfall can be overcome by making use of MoC y nanoparticles, which, depending on the system size and Mo/C atomic ratio, can transform CO 2 into oxygenates and light alkanes. 15,16 Experiments carried out for C-rich MoC 1.1 nanoparticles supported on Au(111) indicated that these new systems are able to dissociate and store significant amounts of hydrogen 17 and to catalyze the CO 2 hydrogenation. 15 Exposing these hydrogenated nanoparticles to CO 2 led to CO with a significant amount of methanol but without producing methane or other alkanes.…”
Section: Introductionmentioning
confidence: 99%
“…15 Exposing these hydrogenated nanoparticles to CO 2 led to CO with a significant amount of methanol but without producing methane or other alkanes. 16 Interestingly, these MoC 1.1 / Au(111) systems are also able to dissociate methane at room temperature. 18 The experiments also evidenced the major role played by the Mo/C atomic ratio, since the C-deficient nanoparticles were very active towards CO 2 but had problems of stability and selectivity, whereas the nearly stoichiometric ones were active, selective and stable.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, under heterogeneous conditions, supported molybdenum carbides or nitrides (i.e., K-Mo 2 C/γ-Al 2 O 3 ) have been found to exhibit high activity and selectivity towards CO or methane production, even at large scale (ca. 1 kg catalyst), with the C/Mo ratio in their structure [29][30][31] (Scheme 1A) playing an important role. In this context, Mo 2 C was used as an efficient catalyst for the selective transfer hydrogenation process of nitroarenes into the corresponding anilines in the presence of hydrazine [32].…”
Section: Introductionmentioning
confidence: 99%